The effect of sports performance and financial performance on European soccer club stock prices - Hendri Prayoga; Fitra Dharma; Dewi Sukmasari (Lighthouse Publishing, 2022)
This study discusses the effect of sports performance and financial performance on the price of European football. This topic is still a hot topic of discussion considering that football is a sport that is starting to develop into a real business industry that has a big impact on society. This phenomenon is caused by many speculations that football can become an industry that is in demand by investors. research conducted from 2016 to 2021 using articles with credible sources. Empirical results show that sports performance has a positive and significant effect on the stock price of football clubs. The liquidity ratio with the Current Ratio indicator has a positive and significant effect on the stock price of football clubs. The solvency ratio with the Debt to Asset Ratio proxy has a negative and significant effect on the stock price of football clubs. However, the profitability ratio with the NPM indicator has no effect on the stock price of the football club. The limitation of this study is that it focuses on European football clubs listed on the Stock Europe Football. Future research is expected to expand the scope of research such as the sample used and measurement indicators. aims to provide more accurate arguments and results regarding the effect of sports performance and financial performance on the stock price of football clubs.